Risk Factors of Osteoporosis in Females: A Hospital-Based Case-Control Study, Yazd, Iran - Maryam Askari; Mohammad Hassan Lotfi; Seyyed Mohammad Azimi; Maral Ostovarfar; Hossein Fallahzadeh; Akram Mehrabbeik; Andishe Hamedi (Tehran University of Medical Sciences, 2022)
Background: The aim of this study was to evaluate the predictors of osteoporosis in women in Yazd, Iran. Methods: This hospital-based case-control study was performed on 270 women 35-65 yr old (135 case and 135 control) from Mar 2016 to Mar 2017. Case and control were matched in terms of age ± 2 (year) as a group matching. Osteoporosis is defined as a T-score of bone mineral density (BMD) below -2.5 SD. Data were analyzed using SPSS 20 software. Statistical tests included chi-square, student t test and Mann Whitney test .Multiple logistic regression (MLR) which forward method was used for modeling. Results: Odds ratio (OR) of osteoprosis were menarche age>12 yr (OR=3.37, CI:2.29-15.89), history of hysterectomy (OR=13, CI:3.81-44.82), rheumatoid arthritis (RA) (OR=6.58, CI:2.29-18.91) calcium supplements (OR=0.14, CI:0.04-0.41), menopause age <40 (OR=11.84, CI:1.54-90), second smoking (OR=3.38, CI:1.16-9.81) and increase of weight (OR=0.86, CI:0.80-0.94). Conclusion: Predictors of osteoporosis was menarche age >12 yr (3 times), history of hysterectomy (13 times), RA (6.5 times), menopause age <40 (12 times), second smoking (more than 3 times), calcium supplements and weight (protective).